Pengembangan Media Pembelajaran Berbasis Android Pada Materi Orientasi Dasar Teknik Jaringan Komputer dan Telekomunikasi di Kelas X TJKT SMK Negeri 1 Kendawangan - Al-Farezi, Gilang; Firdaus, Muhamad; Feladi, Vindo (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to: (1) develop Android-based learning media on the subject of Basic Orientation of Computer Networks and Telecommunications in class X TJKT at SMK Negeri 1 Kendawangan, (2) assess the feasibility of the product based on evaluations by media experts and subject matter experts, and (3) understand student responses to the developed media. This study uses the Research and Development (R&D) method with the ADDIE development model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. In the Analysis stage, the researcher conducts needs analysis through observations and interviews with teachers. In the Design and Development stage, the initial design of the media was created using Android-based software, then validated by two media experts and one content expert using a Likert scale-based assessment instrument. The Implementation stage involved a limited trial on 10 students and a large-scale trial on 30 class X students. Data were collected through questionnaires and analyzed quantitatively descriptively. The results of the validation by media experts and content experts showed scores of 86.1% (in the 'very feasible' category). The small-scale trial obtained a score of 80.9%, while the large-scale trial obtained a score of 87.2% (in the 'very good' category). Thus, this Android-based learning media is deemed feasible and effective for supporting interactive and independent learning.